Psychiatry and neurology in Kharkiv University: historical retrospective - Vovk, Olga (Psychiatry, Neurology and Medical Psychology, 2018)
The present paper provides a fragment of the monograph “School of Medicine of Kharkiv University during the first 100 years of its functioning (1805-1905)” which was published in 1905-1096 under the editing of University professors I.P. Skvortsov and D.I. Bagalii. The text is published according to the rules of modern spelling and punctuation with keeping to the author’s style. The given fragment (the author – Professor Ia. A. Anfimov) covers the main milestones of developing Psychiatry and Neurology as scientific branches and subjects at Kharkiv University in the late XIX – early XX century. There is viewed the personnel, methodological and scientific potential of the Department of systematic and clinical study of nervous diseases established in 1884 as a separate structural unit of Kharkiv University. Special emphasis is given to the characteristic of clinical basis of the department, their material provision, their role and significance for the studying process.